2019
DOI: 10.3390/cells8111452
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 miRNA’s Expression Profile and Its Potential Prognostic Role in Uterine Leiomyosarcoma

Abstract: The lethal-7 (let-7) family is an important microRNA (miRNA) group that usually exerts functions as a tumor suppressor. We aimed to evaluate the expression profile of let-7a, let-7b, let-7c, let-7d, let-7e, let-7f, let-7g, and let-7i and to assess their value as prognostic markers in uterine leiomyosarcoma (LMS) patients. The miRNAs expression profile was assessed in 34 LMS and 13 normal myometrium (MM) paraffin-embedded samples. All let-7 family members showed downregulation in LMS. Our findings showed that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
0
15
0
10
Order By: Relevance
“…Notably, the expression of let-7d in cervical carcinoma cells depends on the expression of human papillomavirus (HPV) E6/E7 oncogene, suggesting a possible partial contribution of this miRNA to HPV-induced cervical carcinoma [ 98 ]. Moreover, a study on 34 leiomyosarcomas and 13 normal myometrium paraffin-embedded samples revealed that low levels of let-7d in leiomyosarcoma were associated with shorter disease-free survival [ 99 ].…”
Section: Let-7d In Additional Gynaecological Malignanciesmentioning
confidence: 99%
“…Notably, the expression of let-7d in cervical carcinoma cells depends on the expression of human papillomavirus (HPV) E6/E7 oncogene, suggesting a possible partial contribution of this miRNA to HPV-induced cervical carcinoma [ 98 ]. Moreover, a study on 34 leiomyosarcomas and 13 normal myometrium paraffin-embedded samples revealed that low levels of let-7d in leiomyosarcoma were associated with shorter disease-free survival [ 99 ].…”
Section: Let-7d In Additional Gynaecological Malignanciesmentioning
confidence: 99%
“…Cilia are specialized microtubule-based cellular organelles that beat in metachronal waves to facilitate the expulsion of inhaled particles and pathogens trapped in the mucus layer from the airway 33 . To detect cilia, immunofluorescence was performed for acetylated α-tubulin and the ARL13B protein 34 . Ciliated cells are defined by their multiple motile apical cilia and by the presence of motor proteins that mediate directional beating, which is critical for MCC 35 .…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the statistical differences among frequencies of each variable, the Chi-square test or Fisher’s exact test was used. The mean and SD (mean ± SD) were used to represent the patient’s age, as previously described [ 87 ]. The Kaplan–Meier method evaluated patient outcome, and the differences between each group were analyzed using the log-rank test (Mantel-Cox) and multivariate analysis with Cox’s regression test by the Cox proportional hazard model.…”
Section: Methodsmentioning
confidence: 99%
“…DFS was determined from the date of surgery to the date of relapse or the last follow-up. Spearman’s rank correlation coefficient was used to measure the strength of the linear relationship between two non-parametric variables, as described elsewhere [ 87 , 88 ]. Statistical analysis was performed using the SPSS (v21, IBM Corp., Armonk, NY, USA) and Graph Pad Prism 5.0 (v3, GraphPad Software Inc., San Diego, CA, USA) software [ 87 ].…”
Section: Methodsmentioning
confidence: 99%